14-3-3 is a VP3-binding protein involved in Macrobrachium rosenbergii Taihu virus infection in shrimp. (September 2021) - Pan, Xiaoyi; Gao, Qiang; Shen, Jinyu; Xu, Ting
Abstract: Macrobrachium rosenbergii Taihu virus (MrTV) is a fierce pathogen that causes high mortality in M. rosenbergii larvae. Little is known about the pathogenesis of MrTV and host-virus interactions. In this study, a virus overlay protein binding assay (VOPBA), followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, was carried out to search for novel host molecules that bind with VP3, one of the main capsid proteins of MrTV. Macrobrachium rosenbergii 14-3-3 protein (Mr14-3-3) was identified as the binding protein of VP3, which was further confirmed by co-immunoprecipitation (Co-IP) and co-localization assay. A preincubation assay was developed, which indicated that preincubation with recombinant Mr14-3-3 (rMr14-3-3) could significantly decrease the expression level of VP3 in MrTV-infected M. rosenbergii larvae, suggesting that preincubation with rMr14-3-3 could partially block MrTV infection. This study revealed that Mr14-3-3 acts as a binding protein for MrTV–VP3 and plays an important role in MrTV infection, offering a potential target for the development of anti-MrTV therapies. Highlights: We firstly identified Mr14-3-3 as a binding protein of MrTV-VP3. Co-IP assay further confirmed the interaction between Mr14-3-3 and MrTV. Confocal microscopy revealed the co-localization of MrTV and Mr14-3-3. Preincubation with rMr14-3-3 can significantly reduce the infection dose of MrTV.